Studies on Length-weight and Length-length Relationships of a Cold Water Fish Neolissochilus hexagonolepis (McClelland) from Tamor River, Nepal - Subba, S.; Adhikaree, S. (Our Nature, 2012)
Present paper attempts to describe length-weight (LW) and total length-standard length (TL and SL) total length and forkal length relationships of cold water fish Neolissochilus hexagonolepis. Fish of different length and weight were caught using cast net and scoop net at Mulghat vicinity, Dhankuta. The fish were kept in ice box in fresh condition and brought to fish laboratory, Department of Zoology, Post Graduate Campus, Biratnagar .The measurement of the fish samples was done with maximum accuracy. The data obtained from measurement were analysed using the formula W = aLb. The b values estimated for the total length and standard length in relation to body weight were 3.056 and 3.063, respectively. The values of b clearly indicate the isometric growth pattern.For total length, standard length and forkal length relationships, the linear values of b were 0.103 and -0.299. Similarly for the relationship between the forkal length and standard length the linear value of b was 0.346. DOI: http://dx.doi.org/10.3126/on.v9i1.5748